Calibration of PKA meters against ion chambers of two geometries - Almeida Jr, José N.; Terini, Ricardo A.; Pereira, Marco A. G.; Herdade, Silvio B. (Revista Brasileira de Física Médica, 2015)
Kerma-area product (KAP or PKA) is a quantity that is independent of the distance to the X-ray tube focal spot and that can be used in radiological exams to assess the effective dose in patients. Clinical KAP meters are generally fixed in tube output and they are usually calibrated on-site by measuring the air kerma with an ion chamber and by evaluating the irradiated area by means of a radiographic image. Recently, a device was marketed (PDC, Patient Dose Calibrator, Radcal Co.), which was designed for calibrating clinical KAP meters with traceability to a standard laboratory. This paper presents a metrological evaluation of two methods that can be used in standard laboratories for the calibration of this device, namely, against a reference 30 cc ionization chamber or a reference parallel plates monitor chamber. Lower energy dependence was also obtained when the PDC calibration was made with the monitor chamber. Results are also shown of applying the PDC in hospital environment to the cross calibration of a clinical KAP meter from a radiology equipment. Results confirm lower energy dependence of the PDC relatively to the tested clinical meter.